The God who gives generously honour, praise and the agony of celebrity - Stephens, Mark B. 1977-; Deal, Georgiane (2018)
The need for honour, meaning publicly acknowledged worth, has been a feature of social life across the ages. From the ancient world of Greece and Rome, through to the honour codes of contemporary celebrity culture, the quest for honour is often framed in agonistic terms, in that honour is a limited good that demands competitive behaviour. This article examines the way early Christianity responded to ancient honour codes, with a view to its potential relevance in contemporary culture. It demonstrates the way early Christianity retained something of the language of honour in its ecclesial communities, but redefined honour in light of its conception of grace.
Keywords: Grace; Honour; Humility; Pride; Spiritual Gifts